Studies of genetic variability and association of yield traits and YVMV disease in Abelmoschus species - YADAV, R K; BADIGER, MAHESH; LATA, SUMAN (The Indian Journal of Agricultural Sciences, 2019)
Germplasm (44) from 6 wild Abelmoschus species and 4 cultivars from cultivated species [Abelmoschus esculentus (L.) Moench] were evaluated during kharif 2015 and 2016 to assess the genetic variability and character association in yield attributes and YVMV disease. Significant differences among accessions for mean performance with respect to 13 quantitative traits revealed presence of sufficient variation in the experimental material used. Mean Percent Disease Incidence (PDI) YVMV, revealed lowest PDI in A. moschatus (IC-141055) (7.73%) followed by IC90476- 1(8.61%) and IC47092 (11.0%). These wild accessions indicated their scope in future breeding programs for resistance to BYVMV. Estimates of genotypic coefficients of variability (GCV) and phenotypic coefficients of variability (PCV) ranged from 6.15-59.14 and 13.98- 62.13 respectively. Heritability in broad sense (h2), genetic advance (GA) and genetic advance as percentage of mean (GAM) ranged from 19-98%, 0.40-84.20, 5.58- 98% respectively. Further classification revealed high GCV (>20.00%), high heritability (>60.00%) and high GAM (>20.00%) for most of the yield components and PDI of BYVMV, except for first flowering node and stem diameter. Character association study publicized significant positive association and high positive direct effect of fruit weight (0.85), number of fruits per plant (0.532), stem diameter (0.088), plant height (0.069) and fruit diameter (0.046) on fruit yield per plant. Therefore, direct selection based on these combinations of traits help in harnessing their positive direct effects on yield per plant in okra improvement programmes.